A new method for concomitant evaluation of drug combinations for their antimicrobial properties - Syed Ahmed Rizvi; Kaniz F Chowdhury; Chiara Borsetto; Emma R Travis; Mohammad Saif; Vikar Ahmed; Laura J Carter; Iqbal Ahmad; Alan McNally; Qazi Mohd Rizwanul Haq (MethodsX)
Microbial pathogens have developed resistance mechanisms to almost every antibiotic available. There is a need to synthesize or screen new natural compounds to combat the development of drug-resistant pathogens. One of the commonly used methods to evaluate the antimicrobial activity of two or more antibiotics involves a checkerboard assay, which is cumbersome, time-consuming, and expensive. We have developed a quick, reliable, and cost-effective method to evaluate the antimicrobial effect of two or more antibiotics at fixed doses with different concentrations of a novel natural ingredient or test compound.The technique involves the following steps: • Preparation of a bacterial culture of the test strain at 0.5 McFarland standard (0.1 OD at 600 nm), and preparation of stock solutions for the chemical of interest and standard drugs. • The required amount of all three components can be dispensed into respective wells of a microplate using multichannel pipette. • Optical density (OD) values obtained would be directly related to the individual as well as combined effect of compounds on the given bacterial strain.